Optimalisasi Bandwidth Menggunakan Metode Queue Tree Dan Web Filtering Berbasis Router Mikrotik Pada SMK Assa’adah - Ahmad Doni; Lisda Amalia; Verolia Yunita Putri; Saprudin (CV. Shofanah Media Berkah, 2023)
In the current era, the internet has become an inseparable part of everyday life. Sources of information needed can be easily obtained through the internet. Many places, including cafes, campuses, and schools, provide internet access for their users. The use of the internet in the school environment is very important because many things have turned to the digital realm, such as e-books, online classes, and even digital libraries. At Assa'adah Jakarta Vocational School, there are internet facilities that are shared by teachers and students without any bandwidth management or restrictions on access to social media. As a pesantren-based school, students are not allowed to use gadgets except in certain situations, such as holidays or when there are school assignments. However, when students are allowed to use the internet, students often abuse it by opening social media, playing online games, or accessing content that interferes with the teaching and learning process. Bandwidth management is important for controlling bandwidth usage by users. If unchecked, excessive bandwidth usage by one or more users may result in less bandwidth allocation for other users. As a result, the network cannot provide maximum service to all users. In this final project, the writing methodology used includes literature study to collect data sources and related references, observation to directly observe the network system to be built, and interviews as a communication process between the writer and the respondents to obtain information, opinions or responses related to the topics discussed. researched.